Squamous–columnar junction of Von Ebner’s glands may be a significant origin of squamous cell carcinomas in the base of the tongue - Chen, Peng-Ning; Chen, Xin-Yu; Chen, Guan-Xi; Luo, Lin; Yan, Qi-Zhang; Ruan, Ping; Li, Ping; Yu, Da-Hai (Frontiers in Oncology, 2022)
Objectives: The histological origin of base of the tongue (BOT) carcinomas is still elusive, and most studies have been focusing on lingual tonsil. In this study, we sought to define the existence of the squamous-columnar junction (SCJ) in the human Von Ebner's glandular duct and explored the potential of that in forming squamous cell carcinomas in BOT. Materials and methods: The specific genomes of BOT carcinoma were acquired and screened out by TCGA database analysis. The 4-nitroquinoline-1-oxide(4-NQO)-treated mouse model was used to explore the transformation of SCJ during cancerization. We used immunohistochemistry to confirm the characteristics of SCJ in human Von Ebner's gland, which were further compared with those in anus and cervix. Results: SCJ in the human Von Ebner's glandular duct was found to be similar to that of the cervix and anus. In 4-NQO-treated mouse model, transformation zone was found, which is transformed from SCJ by squamous metaplasia. In human, the transformation zone of Von Ebner's gland is also similar to that of cervix and anus. Conclusion:  It is the first time that the existence of SCJ in the opening of the human Von Ebner's glandular duct was confirmed. SCJ of Von Ebner's glands maybe a significant origin of squamous cell carcinomas in BOT.